Świadomość własnego procesu uczenia się języków obcych przyczynkiem do innowacyjnych działań dydaktycznych. W stronę dydaktyki wielojęzyczności w początkowym kształceniu nauczycieli - Kucharczyk, Radosław; Szymankiewicz, Krystyna (Neofilolog, 2019)
The aim of this article is to reflect on the initial training of teachers in line with the assumptions of multilingual didactics. A definition of plurilingual competence is given at the beginning of this article. We then discuss briefly about the main assumptions of plurilingual teaching. The next part of the article deals with the philosophy of educating future foreign language teachers in philological studies, which should be largely based on reflection. The article concludes with the analysis of data obtained from students participating in teacher education classes. The aim of the study was to diagnose whether the self-awareness of potential subjects, as given to them by the multilingual competence, could contribute to innovative teaching.